Circulating tumour cells predict survival in gastric cancer patients: a meta-analysis - Wang, Hui-Yu; Wei, Jia; Zou, Zheng-Yun; Qian, Xiao-Ping; Liu, Bao-Rui (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : The prognostic value of the detection of circulating tumour cells (CTCs) in gastric cancer has been studied intensely in recent years. However, the application of different technologies led to inconsistent results between the studies. Here, we performed a meta-analysis of published studies to summarise the evidence. Material and methods : Medline and ISI Web of Knowledge were searched up to March 2013 using “circulating tumor cells” and “gastric cancer” as search terms. Hazard ratio (HR) with 95% confidence intervals (CIs) for prognostic outcomes and clinical characteristics were extracted from each study. Pooled hazard ratios (HR) and odds ratios (OR) were calculated using random or ﬁxed-effects models. Results: Twelve studies enrolling 774 patients were included. The combined HR estimate for overall survival (OS), disease-free survival (DFS), and progression-free survival (PFS) were 1.41 (95% CI: 1.28–1.62), 2.99 (95% CI: 2.01–4.45) and 1.64 (95% CI: 1.02–2.62), respectively. Subgroup analysis concerning detection methods and sampling time showed that results of RT-PCR for the OS group and RT-PCR for the DFS group suggest a prognostic significance of CTC detection (pooled HR [95% CI]: 1.45 [1.28–1.65], I 2 = 38%, p = 0.13; 2.99 [2.01–4.45], I 2 = 0%, p = 0.32). In addition, results of the baseline CTC detection group also indicated a significant prognostic value to predict OS and DFS (pooled HR [95% CI]: 1.47 [1.19–1.82], I 2 = 38%, p = 0.14; 2.99 [2.01–4.45], I 2 = 0%, p = 0.32). We simultaneously found that the detection of CTCs correlated with pathological stage (pooled OR [95% CI]: 2.95 [1.65–5.28], I 2 = 56%, p = 0.03), lymph node status (pooled OR [95% CI]: 2.26 [1.50–3.41], I 2 = 37%, p = 0.09), the depth of invasion (pooled OR [95% CI]: 3.21 [1.38–7.43], I 2 = 72%, p = 0.002), and distant metastasis (pooled OR [95% CI]: 2.68 [1.25–5.73], I 2 = 43%, p = 0.15). Conclusions : Detection of CTCs is associated with poorer prognosis in gastric cancer patients.